Transformasi Sastra Arab Kontemporer di Era Jurnalisme dan Media Digital - Badawi, Hendry; Muhsin, Muhsin; Khalik, Muhammad Fihris (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to analyze the relationship between journalism and the development of modern Arabic literature, including journalism's influence on literary writing styles and the transformation of this relationship in the digital media era. The study employs a qualitative library research method, using documentation and content analysis techniques to examine relevant literature. The findings indicate that journalism plays a strategic role in shaping the development of Arabic literature by providing a public space for writers, fostering aesthetic innovations, and influencing changes in writing techniques and narrative structures. The interaction between journalistic and literary discourses has given rise to hybrid forms that enrich the representation of social reality while expanding literature's function as a medium for reflection and critique. Furthermore, the evolution of digital media has altered the patterns of production, distribution, and consumption of literary works, resulting in forms of literature that are more interactive, multimodal, and participatory; however, this shift also presents new challenges regarding meaning-making, the dominance of visual culture, and the influence of algorithms on the dissemination of works. The study concludes that the relationship between journalism and Arabic literature is dynamic and transformative, necessitating the development of contemporary Arabic literary studies through an interdisciplinary approach—integrating perspectives from literature, media, and communication—to understand the changing literary ecosystem in the digital age.